Campus Canopy, 1944-03-28 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1944)
Ruth Page, famed dancer, Presents Concert Tomorrow Night Ether A. Oldt, Antioch Voice Teacher Will Visit GSWC Campus -- Twent-Three Girls Make Dean's List -- Thompson Elected Frosh Sec.-Treas -- A Typical Student Observes The New dining Hall System
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals